Sosialisasi Senam Komering Sebagai Program Edukasi Kebugaran Berbasis Budaya di SMP Quraniah 1 Palembang - Alfadillah, M Fathir; Melianty, Selvi; Sukmawati, Noviria (Jambura Arena Pengabdian, 2025)
This community service program aimed to socialize Komering Gymnastics as a culture-based fitness education program at SMP Quraniah 1 Palembang. The program was motivated by low student participation in structured physical activities and a declining appreciation of local culture. Komering Gymnastics, which adapts traditional movement patterns of the Komering community in South Sumatra, was utilized as a medium to integrate cultural values into physical education (PJOK) learning. The program was implemented over four months, from August 2025 to November 2025, involving 16 students through stages of socialization, guided practice, mentoring, and evaluation. Data were collected using observation, questionnaires, interviews, documentation, and simple physical fitness tests. The results indicated an increase in student activeness, improved understanding of local cultural values, and enhancements in physical fitness components, including coordination, flexibility, and endurance. Teachers and school stakeholders responded positively, noting that the program enriched PJOK learning and strengthened students’ cultural identity. This program concludes that Komering Gymnastics is feasible as an alternative culture-based fitness education program in junior high schools.